2009
DOI: 10.1097/mcd.0b013e32832d06d7
|View full text |Cite
|
Sign up to set email alerts
|

Congenital anterolateral bowing of the tibia with ipsilateral polydactyly of the great toe associated with cerebral cyst: a new entity?

Abstract: We present two patients with congenital anterolateral bowing of the tibia with polydactyly who had, in addition, cerebral malformations including agenesis of the corpus callosum and a large cerebral cyst. We discuss phenotypic overlap with the acrocallosal syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
2
3
0
2
Order By: Relevance
“…Case 19 presented a rare and challenging situation for estimation of the prognosis because sonography and further characterization by 3D techniques showed medial deviation of an enlarged first toe in a rectangular position (Figure 8, A and B), with toe duplication not excluded, anterior bowing of the right tibia with possible pseudarthrosis (Figure 8D), and unilateral pes equinovarus without other sonographic findings in the 22nd week of pregnancy. Although the findings might suggest an isolated complex local malformation, an association with cerebral malformations and developmental impacts has been described 17 . Postmortem examination confirmed prenatal findings (Figure 8, C, E, and F), and histologic examination after pregnancy termination revealed duplication of the bone marrow cavity of the right tibia, matching previous morphologic findings obtained during surgery in a similar case 18 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Case 19 presented a rare and challenging situation for estimation of the prognosis because sonography and further characterization by 3D techniques showed medial deviation of an enlarged first toe in a rectangular position (Figure 8, A and B), with toe duplication not excluded, anterior bowing of the right tibia with possible pseudarthrosis (Figure 8D), and unilateral pes equinovarus without other sonographic findings in the 22nd week of pregnancy. Although the findings might suggest an isolated complex local malformation, an association with cerebral malformations and developmental impacts has been described 17 . Postmortem examination confirmed prenatal findings (Figure 8, C, E, and F), and histologic examination after pregnancy termination revealed duplication of the bone marrow cavity of the right tibia, matching previous morphologic findings obtained during surgery in a similar case 18 .…”
Section: Discussionsupporting
confidence: 77%
“…Although the findings might suggest an isolated complex local malformation, an association with cerebral malformations and developmental impacts has been described. 17 Postmortem examination confirmed prenatal findings (Figure 8, C, E, and F), and histologic examination after pregnancy termination revealed duplication of the bone marrow cavity of the right tibia, matching previous morphologic findings obtained during surgery in a similar case. 18 In general, 3D sonography is not mandatory for assessing fetal limbs but, as in this situation, has shown advantages in characterizing limb anomalies.…”
Section: Filges Et Al-fetal Polydactyly On Prenatal Sonographysupporting
confidence: 83%
“…The associated deformities are summarized in Table I. Ten cases had abnormality of the hand, one had mild equinovarus, two had duplicated metatarsal bones (including our patient 1), one had a duplicated navicular and cuneiform, and two had major cerebral malformations [Newell and Durbin, 1976; Adamsbaum et al, 1991; Watanabe et al, 1992; Weaver et al, 1996; Kitoh et al, 1997; Bressers and Castelein, 2001; Manner et al, 2005; Lemire, 2007; Breckpot et al, 2009]. All of our patients and several published cases had no associated deformities.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, all cases were unilateral and related to the tibial field [Lewin and Opitz, 1986; Al‐Awadi et al, 1987; Khoury et al, 1999]. Given the skewed sex ratio in both acrocallosal syndromes and CABTP, and their marked clinical overlap, Breckpot et al [2009] suggested that the two conditions are manifestations of a single disorder with variable expression. We agree with the opinion of Adamsbaum et al [1991], Weaver et al [1996], and Lemire [2007] that the deformity is more likely to be a developmental abnormality than a genetically transmitted disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation